Changes in the Human Gut Microbiota Associated With Colonization by Blastocystis sp. and Entamoeba spp. in Non-Industrialized Populations - Even, Gaël; Lokmer, Ana; Rodrigues, Jules; Audebert, Christophe; Viscogliosi, Eric; Ségurel, Laure; Chabé, Magali (Frontiers in Cellular and Infection Microbiology, 2021)
Human gut microbial communities are mainly composed of bacteria, but also include fungi, viruses, archaea, and protozoa, whose role in the gut ecosystem has only recently begun to be recognized. For example, humans colonized by Blastocystis (a gut protozoan with controversial pathogenicity) host a more diverse bacterial microbiota than individuals not carrying it, suggesting that its presence may be beneficial for the host. In parallel, the presence of non-pathogenic Entamoeba spp. has been associated with an increased diversity and compositional shifts in the bacterial microbiota of healthy rural individuals in Cameroon. However, Entamoeba and Blastocystis, the two most prevalent human gut protozoa, have never been studied in the same individuals, preventing the study of their interaction. As Blastocystis is one of the few gut protozoa commonly found in industrialized populations, which are otherwise mostly devoid of gut eukaryotes, we need to focus on rural “traditional” populations, who harbor a higher diversity of gut eukaryotes (whether pathogenic or commensal) in order to study protozoa interactions in the gut ecosystem. To this end, we profiled the gut bacterial microbiota of 134 healthy Cameroonian adults using 16S rRNA gene amplicon sequencing data. Entamoeba and Blastocystis presence and co-occurrence pattern in the same individuals were determined using metagenomic shotgun data. We found that, when taking into account both protozoa jointly, Blastocystis was associated with both a higher richness and a higher evenness of the gut bacterial microbiota, while Entamoeba was associated only with a higher richness. We demonstrated a cumulative influence of these protozoa on bacterial microbiome diversity. Furthermore, while the abundance of several common taxa (for example, Ruminococcaceae, Coprococcus and Butyrivibrio) varied according to Blastocystis¬ colonization, only a single Bacteroides amplicon sequence variant was found to be differentially abundant between Entamoeba-negative and Entamoeba-positive samples. Given the specific signature of each protozoan on the gut microbiota and the seemingly stronger association for Blastocystis, our results suggest that Blastocystis and Entamoeba interact with gut bacteria each in its own way, but experimental studies are needed to explore the precise mechanisms of these interactions.